To solve the equation \( 9x + 7x + 8 = -4 + 4(3x + 5) \), we can start simplifying both sides.
First, combine like terms on the left side:
\[ 9x + 7x = 16x \] Thus, the left side becomes:
\[ 16x + 8 \]
Next, let's simplify the right side of the equation:
\[ -4 + 4(3x + 5) \] Distributing the \(4\) gives:
\[ 4 \cdot 3x + 4 \cdot 5 = 12x + 20 \] So the right side simplifies to:
\[ -4 + 12x + 20 = 12x + 16 \]
Now we can rewrite the equation as:
\[ 16x + 8 = 12x + 16 \]
Next, we will isolate \(x\). Subtract \(12x\) from both sides:
\[ 16x - 12x + 8 = 16 \] This simplifies to:
\[ 4x + 8 = 16 \]
Next, subtract \(8\) from both sides:
\[ 4x = 16 - 8 \] Which simplifies to:
\[ 4x = 8 \]
Now, divide both sides by \(4\):
\[ x = 2 \]
This gives us one solution: \(x = 2\).
Since there is only one solution, we conclude:
One solution.